Leopard ( Panthera pardus ) status, distribution, and the research efforts across its range - Jacobson, Andrew P.; Gerngross, Peter; Lemeris Jr, Joseph R.; Schoonover, Rebecca F.; Anco, Corey; Breitenmoser-Würsten, Christine; Durant, Sarah M.; Farhadinia, Mohammad S.; Henschel, Philipp; Kamler, Jan F.; Laguardia, Alice; Rostro-García, Susana; et al. (PeerJ (San Francisco, CA), 2016)
The leopard’s ( Panthera pardus ) broad geographic range, remarkable adaptability, and secretive nature have contributed to a misconception that this species might not be severely threatened across its range. We find that not only are several subspecies and regional populations critically endangered but also the overall range loss is greater than the average for terrestrial large carnivores. To assess the leopard’s status, we compile 6,000 records at 2,500 locations from over 1,300 sources on its historic (post 1750) and current distribution. We map the species across Africa and Asia, delineating areas where the species is confirmed present, is possibly present, is possibly extinct or is almost certainly extinct. The leopard now occupies 25–37% of its historic range, but this obscures important differences between subspecies. Of the nine recognized subspecies, three ( P. p. pardus, fusca, and saxicolor ) account for 97% of the leopard’s extant range while another three ( P. p. orientalis, nimr, and japonensis ) have each lost as much as 98% of their historic range. Isolation, small patch sizes, and few remaining patches further threaten the six subspecies that each have less than 100,000 km 2 of extant range. Approximately 17% of extant leopard range is protected, although some endangered subspecies have far less. We found that while leopard research was increasing, research effort was primarily on the subspecies with the most remaining range whereas subspecies that are most in need of urgent attention were neglected.